A preliminary study on identifying specific risk factors of post-partum depression - Shafi, Afiya M.; Jain, Rohit; Pandey, Smita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Pregnancy and childbirth are important events in the life of a woman and also highly vulnerable period of various physiological and psychological illnesses. Several literatures propound that 22% young Indian mothers are showing depressive symptoms after delivery. The consequence of maternal depression is adverse both for mother and development of the child. Objective of this study was to examine the social and obstetric factors contributing post-partum depression. Methods: Women, 18-35 years of age, having four days to one-year postpartum period was taken from the tertiary care hospital settings. Terminal illness, still birth delivery and comorbid psychiatric illness was excluded. Screening and diagnosis of postpartum depression done based on international classification of diseases (ICD 10) using Edinburgh post-natal depression scale (EPDS). A comparative approach by the means of descriptive statistics was implied for data analysis where mothers with depressive symptoms are experimental group and non-depressed mothers were acted as the controls. Results: Study findings indicated a statistically significant association between postpartum depression and risk factors such as occupation and average social economic class, first time delivery. Conclusions: It is a preliminary study in a restricted geographical area, not covering the neurobiological risk factors of postpartum depression. Hence, the future study will focus on the large sample size in a multi areal population for assuring the accuracy of the result.